Carapace microbiota in American lobsters (Homarus americanus) associated with epizootic shell disease and the green gland - Schaubeck, Anna; Cao, Dianjun; Cavaleri, Vincent; Mun, Seyoung; Jeon, Soo Jin (Frontiers in Microbiology, 2023)
Epizootic Shell Disease (ESD) has posed a great threat, both ecologically and economically, to the American lobster population of Long Island Sound since its emergence in the late 1990s. Because of the polymicrobial nature of carapace infections, causative agents for ESD remain unclear. In this study, we aimed to identify carapace microbiota associated with ESD and its potential impact on the microbiota of internal organs (green gland, hepatopancreas, intestine, and testis) using high-throughput 16S rRNA gene sequencing. We found that lobsters with ESD harbored specific carapace microbiota characterized by high abundance of Aquimarina, which was significantly different from healthy lobsters. PICRUSt analysis showed that metabolic pathways such as amino acid metabolism were enriched in the carapace microbiota of lobsters with ESD. Aquimarina, Halocynthiibacter, and Tenacibaculum were identified as core carapace bacteria associated with ESD. Particularly, Aquimarina and Halocynthiibacter were detected in the green gland, hepatopancreas, and testis of lobsters with ESD, but were absent from all internal organs tested in healthy lobsters. Hierarchical clustering analysis revealed that the carapace microbiota of lobsters with ESD was closely related to the green gland microbiota, whereas the carapace microbiota of healthy lobsters was more similar to the testis microbiota. Taken together, our findings suggest that ESD is associated with alterations in the structure and function of carapace microbiota, which may facilitate the invasion of bacteria into the green gland.